Naomi Klein - Bonobo Films; Soundview Media Partners ([United States] : Bonobo Films, 2009)
This documentary features Naomi Klein explaining the ideas and research behind her bestselling book, The shock doctrine: The rise of disaster capitalism. In this riveting lecture and interview, Klein challenges and exposes the popular myth of the free market economyʼs peaceful global victory.
In English.
Online resource; title from opening/closing credits (Digitalia Film Library, viewed August 30, 2017).
Keywords: Klein, Naomi, -- 1970-; Klein, Naomi, -- 1970- -- Interviews; Business ethics; Capitalism -- Moral and ethical aspects; Financial crises; Free enterprise -- Moral and ethical aspects; International economic relations; Filmed lectures; Filmed interviews; Documentary films; Internet videos; Nonfiction films; Streaming video